COMPREHENSIVE MANAGEMENT PLAN FOR THE ALTERNATIVE LEARNING SYSTEM (ALS) IN THE DIVISION OF BATANGAS CITY - Ebora, Meniano D.; Guillo Jr., Romeo M. (International Journal of Research -GRANTHAALAYAH, 2018)
The study aimed to propose a comprehensive management plan for the Alternative Learning System (ALS) program in the Division of Batangas City. The study used descriptive method of research using a researcher-constructed questionnaire, interview, and Focus Group Discussion (FGD). It involved 30 ALS implementers and 350 ALS graduates from CY 2009 to CY 2013 selected through stratified random sampling. Results showed that among the ALS program offerings, Literacy Volunteer Program and Balik-Paaralan Para sa Out-of-School Adults (BPOSA) were extremely evident. Lecture-demonstration as a teaching strategy was most often utilized by the ALS implementers. The classrooms for ALS instruction and the learning modules were very much adequate for ALS instruction. The paper and pencil test was very much applicable to the type of ALS learners. The data revealed that 221 of the 350 respondents were studying in the different colleges and universities and in TESDA while 129 ALS graduates were already working in the different firms or industries. From the results, the researcher based the output of the study which is a proposed comprehensive management plan that may help strengthen the ALS program in the division and benefit stakeholders such as ALS implementers, Local Government Units, DepEd/school officials, and ALS learners.